Current Surgical Therapy of Locally Advanced cSCC: From Patient Selection to Microsurgical Tissue Transplant. Review - Brambullo, Tito; Azzena, Gian Paolo; Toninello, Paolo; Masciopinto, Giuseppe; De Lazzari, Alberto; Biffoli, Bernardo; Vindigni, Vincenzo; Bassetto, Franco (Frontiers in Oncology, 2021)
Among the non-melanoma skin cancers (NMSC) the squamous cell carcinoma (SCC) is one of the most challenging for the surgeon. Local aggressiveness and a tendency to metastasize to regional lymph nodes characterize the biologic behavior. The variants locally advanced and metastatic require wide excision and node dissection. Such procedures can be extremely detrimental for patients. The limit of the surgery can be safely pushed forward with a multidisciplinary approach. The concept of skin oncoplastic surgery, the ablative procedures and the reconstructive options (skin graft, pedicled flap, microsurgical free flap) are discussed together with a literature review.